2020
DOI: 10.2147/dmso.s267790
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug-Related Problems and Their Predictors Among Patients with Diabetes Attending the Ambulatory Clinic of Gebre Tsadik Shawo General Hospital, Southwest Ethiopia</p>

Abstract: Background: Patients with diabetes are vulnerable to experiencing drug-related problems. Thus, this study aimed to assess drug-related problems and their predictors among patients with diabetes attending the ambulatory clinic of Gebre Tsadik Shawo General Hospital. Methods: A cross-sectional study was conducted from September 1, 2019 to November 30, 2019. Drug-related problems were identified using the Pharmaceutical Care Network Europe version 5.01. Patient's written informed consent was obtained after explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
3
8
0
2
Order By: Relevance
“…Additionally, participants who had a T2DM duration of less than 1 year were 63% less likely to have IADT compared to patients with a T2DM duration of more than 10 years (AOR, 0.37; 95% CI, 0.11–0.35; P-value = 0.019). This finding is similar to a study in Ethiopia [ 31 ], India [ 62 ], and Pakistan [ 34 ]. This might be because those patients with a longer duration of diabetes had a higher chance of developing diabetes complications which contribute to drug-drug interactions and multiple drug therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, participants who had a T2DM duration of less than 1 year were 63% less likely to have IADT compared to patients with a T2DM duration of more than 10 years (AOR, 0.37; 95% CI, 0.11–0.35; P-value = 0.019). This finding is similar to a study in Ethiopia [ 31 ], India [ 62 ], and Pakistan [ 34 ]. This might be because those patients with a longer duration of diabetes had a higher chance of developing diabetes complications which contribute to drug-drug interactions and multiple drug therapy.…”
Section: Discussionsupporting
confidence: 92%
“…This might be because those patients with a longer duration of diabetes had a higher chance of developing diabetes complications which contribute to drug-drug interactions and multiple drug therapy. In addition, these patients are likely to have comorbid conditions which influence the desired outcome of other diseases by increasing the number of drugs, causing drug-drug, drug-disease, and disease-disease interactions which collectively resulted in increased likelihood of experiencing DRP in the study patients [ 31 – 34 ]. It was also found that patients with HbA1c of less than 7% during the current admission had 9.97 times higher (AOR, 9.97; 95% CI, 2.34–13.57; P-value = 0.002) odds of experiencing IADTs compared to patients with HbA1c of greater or equal to 7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings revealed that drug interaction (53; 45.3%) was the most commonly identified drug-related problem in diabetic patients. These results are parallel with the findings of the study conducted in Southern Ethiopia [15]. The reason might be due to diabetic patients having a high rate of cardiovascular, neurological, ophthalmic, renal, and thyroid complications than non-diabetic patients.…”
Section: Discussionsupporting
confidence: 88%
“…Continuous and timely assessment of ADRs is very important to provide appropriate interventions in diabetic patients. These findings are nearly similar to the study conducted in Addis Ababa, and Ethiopia [15,17]. Other DRPs include untreated indication (17.9%), failure to receive drugs (5.1%), improper drug selection (4.3%), overdose (3.4%), underdose (2.6%), and drug use without indication (0.8%).…”
Section: Discussionsupporting
confidence: 83%